Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 11 - Review Exercises - Page 841: 61



Work Step by Step

$\displaystyle \sum_{k=1}^{∞}4(\frac{2}{3})^{k-1}=4(\frac{2}{3})^{0}+4(\frac{2}{3})^{1}+4(\frac{2}{3})^{2}...$ $a_1=4(\frac{2}{3})^{0}=4$ $r=\frac{a_2}{a_1}=\frac{4(\frac{2}{3})^{1}}{4(\frac{2}{3})^{0}}=\frac{2}{3}$ $S=\frac{a_1}{1-r}=\frac{4}{1-\frac{2}{3}}=\frac{4}{\frac{1}{3}}=12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.